Tackling cybercrime – the UK response. Issue 1 (2nd January 2017) - Saunders, Jamie
ABSTRACT: Cybercrime activity is growing fast and evolving at a rapid pace, becoming both more technically proficient and aggressive. The Office for National Statistics (ONS) estimates that there were two million computer misuse offences experienced in England and Wales in the 12 months to March 2016. Precise figures for the total cost of cybercrime are hard to establish, but a National Crime Agency (NCA) Assessment published in July 2016 estimated the cost to the UK economy to be in the order of billions of pounds per annum. Tackling the threat of cybercrime requires a broad-based strategy that recognises the diversity of offences, actors and motivations. It requires the right balance between the 'Four Ps' of the UK Serious and Organised Crime Strategy – PURSUE, PREVENT, PROTECT, PREPARE. Critically, it requires close working between law enforcement, government, international partners and industry. This paper sets out the UK approach to tackling cybercrime and outlines some of the successes that have been achieved to date. It recognises that government, law enforcement agencies and other bodies have all increased efforts to tackle cybercrime, but concludes that these efforts alone cannot fully address the challenge. A number of areas are identified that need to be strengthened if, collectively, we are to have a lasting impact on the threat.